Hungry for change [videorecording (DVD)] - Ledesma, Carlos; Bosch, Laurentine ten; Colquhoun, James; Bolton, Nick; Caitlin, James; Carr, Kris (Docuramafilms : Distributed in the U.S. by New Video, 2012)
From the creators of the best-selling documentary Food Matters comes another hard-hitting film certain to change everything you thought you know about food and nutrition. It exposes shocking secrets the diet, weight loss and food industries don't want you to know about deceptive strategies designed to keep you coming back for more. Find out what's keeping you from having the body and health you deserve and how to escape the diet trap forever.